Kinematic and stress analysis of three blade designs for soil aeration roller - Yam-Tzec, José Antonio; Peña-Peralta, Miguel Ángel; Romantchik-Kriuchkova, Eugenio; Morelos-Moreno, Álvaro (REVISTA TERRA LATINOAMERICANA, 2021)
In the present study, the kinematic and stress analysis of an aerator roller with blades was performed. The trajectories of the aerator roller blades were obtained, which included the rotational and translational movements on the ground. Longitudinal underground areas and volumes of the cracks were calculated for rectangular blades (Type A), symmetric triangular (Type 1) and asymmetric triangular (Type 2) blades. The results of the kinematic analysis reported that type A blades significantly modified soil with respect to the other two. Normal forces were calculated numerically and per finite element, obtaining for blade type 1 numerically calculated forces of 4.52 MPa in the upper zone of the element and -7.06 MPa in its lower zone. The normal stress calculated per finite element were found in the range from 3.66 to 6.52 MPa for the upper part of the element and -7.8 MPa for its lower part. For type 2 design, a normal stress was obtained numerically of 8.83 MPa. The normal stress calculated per finite element was found in the range from 3.95 to 12.86 MPa.